Comportamiento Sexual y uso de Anticonceptivos en estudiantes de la Universidad Nacional de San Martín. 1,994 - Gonzales Pizarro, Gladis Ana (1995)
The present work is a basic descriptive study with prospective data collection on students of the National University of San Martin, July - September 1994 for execution descriptive correlational design was used insitu using information based on surveys conducted by the researchers; a sample of 683 students who were selected proportionately from each Faculty Agro, = 142 was taken; Agronomy = 150, Civil Engineering = January 57, OB = 234 After data analysis slight male predominance was found, it was higher in the Faculty of Civil Engineering (80.9%), in verse phenomenon in the Faculty of Obstetrics where predominantly female (72.6%). The average age who received sexual education • is 13.27 with a range of 8-23 school year being the most common site. The SIDA and gonorrhea are the STDs most known 49.0% and 32.1% respectively.